Prevention of airborne disposal from staff in the O.R. reducing the risk of infection: what are the benefits of using clean air suits or scrub suits? - Abreu, Maria José Araújo Marques (2012)
Experts in infection control are often asked about issues related to the use of scrubs and clean air suits in the operating room (OR). So, what are clean air suits and scrub suits? This article seeks to highlight the most relevant information of this products and try to define the benefits of using them for preventing airborne disposal from the surgical staff, reducing the risk of infection. No scientific data support the practice of using scrub suits as a means for preventing transmission of infection, but on the other side we have a vast amount of studies regarding the effectiveness of clean air suits. However this won´t invalidate the use of scrub suits, just validating that this type of studies has to be done for scrubs suits.